2008
DOI: 10.1016/j.ypmed.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Design and baseline characteristics from the KAN-QUIT disease management intervention for rural smokers in primary care

Abstract: Objective-To describe the design, implementation, baseline data, and feasibility of establishing a disease management program for smoking cessation in rural primary care.Method-The study is a randomized clinical trial evaluating a disease management program for smoking cessation. The intervention combined pharmacotherapy, telephone counseling, and physician feedback, and repeated intervention over two years. The program began in 2004 and was implemented in 50 primary care clinics across the State of Kansas.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 55 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…As part of a rural primary care research experience, trained medical students systematically screened patients, identified smokers, and recruited them for this study, regardless of their interest in quitting (12). Smokers were eligible if they had a primary care physician participating in this study, and they were ≥ 18 years of age, smoked ≥ 10 cigarettes/day, smoked for at least one year, smoked at least 25 out of the past 30 days, spoke English, and had a telephone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a rural primary care research experience, trained medical students systematically screened patients, identified smokers, and recruited them for this study, regardless of their interest in quitting (12). Smokers were eligible if they had a primary care physician participating in this study, and they were ≥ 18 years of age, smoked ≥ 10 cigarettes/day, smoked for at least one year, smoked at least 25 out of the past 30 days, spoke English, and had a telephone.…”
Section: Methodsmentioning
confidence: 99%
“…All interventions were conducted from a single central site by one of 9 counselors trained in smoking cessation and motivational interviewing (12). Participants were assigned to counselors without regard to practice site.…”
Section: Methodsmentioning
confidence: 99%
“…Lower SES is a risk factor for smoking, for persistent and is a barrier to access to smoking cessation treatment (Kiefe et al, 1998; Roddy et al, 2006; Schaap and Kunst, 2009; Weinberger et al, 2008). Additionally, clinical trials for smoking cessation generally exclude potential participants with current depression, as well as those with anxiety and substance use disorders, which are highly comorbid with both depression and smoking (Cox et al, 2008; Gierisch et al, 2012). Physical health problems are also commonly excluded, and therefore, clinical trials may be more apt to include “super healthy” smokers who are unlikely to be representative of the general population of smokers in the population.…”
Section: Introductionmentioning
confidence: 99%
“…They are described by Miller and Rollnick [1,8] and have been incorporated into brief MI-based intervention protocols [3,9,10]. Motivation rulers have become popular clinically [11].…”
Section: Introductionmentioning
confidence: 99%